Dome-shaped magnetic order competing with high-temperature superconductivity at high pressures in FeSe - J. P. Sun; K. Matsuura; G. Z. Ye; Y. Mizukami; M. Shimozawa; K. Matsubayashi; M. Yamashita; T. Watashige; S. Kasahara; Y. Matsuda; J. -Q. Yan; B. C. Sales; et al. (Nature Communications, 2016)
The relationship between electronic ordering and superconductivity, crucial to understand high-Tc superconductors, remains elusive. Here, Sun et al. report the pressure-induced dome shape of a magnetic phase superceding the nematic order in FeSe, suggesting competing nature between magnetism and superconductivity.